Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2021)
The present issue of Studies in Second Language Learning and Teaching is the last in the 2021 volume and concludes the eleventh year of the existence of the journal. Looking back, it has been an exceptionally good year for SSLLT. First, we have been receiving a constantly increasing number of submissions and, what is of paramount importance for any journal, most of these submissions have been of very high quality. Second, we are very happy with the scope and quality of the papers that have been published, including those comprising the special issue on teaching English reading and writing to young learners, which was guest-edited by Barry Lee Reynolds and Mark Feng Teng. Third, and perhaps most importantly, not only has SSLLT been finally indexed in the Web od Science, but it is also listed among the 20 best journals in linguistics (18/193), with the impact factor of 3.036 (Q1) (JCR). Achieving this status has been a long and arduous process but at the same time an extremely rewarding journey. Obviously, this undeniable success would not have been possible without all of those who have lent their support to the development of SSLLT from the get-go. My sincere thanks go to Associate Editors, all the guest editors of special issues, members of the Editorial Board, the many hundreds of reviewers and, first and foremost, to all the amazing authors who have chosen SSLLT as a venue for their work. I can assure all of you that we will not be resting on our laurels and will do everything in our power to keep up the good work to further enhance the position of SSLLT in the field. We are also hoping to be able to celebrate its success with a face-to-face conference to be held in Kalisz, Poland in October 2022. We are currently working on the call for papers and we are planning to send it out in the next month or so.